Recombinant Tissue-Type Plasminogen Activator Plus Eptifibatide Versus Recombinant Tissue-Type Plasminogen Activator Alone in Acute Ischemic Stroke: Propensity Score-Matched Post Hoc Analysis. Issue 2 (February 2015) - Adeoye, Opeolu; Sucharew, Heidi; Khoury, Jane; Tomsick, Thomas; Khatri, Pooja; Palesch, Yuko; Schmit, Pamela A.; Pancioli, Arthur M.; Broderick, Joseph P.
Abstract : Background and Purpose—: The Combined Approach to Lysis Utilizing Eptifibatide and rt-PA in Acute Ischemic Stroke-Enhanced Regimen (CLEAR-ER) trial demonstrated safety of recombinant tissue-type plasminogen activator (r-tPA) plus eptifibatide in acute ischemic stroke (AIS). CLEAR-ER randomized AIS patients (5:1) to 0.6 mg/kg r-tPA plus eptifibatide versus standard r-tPA (0.9 mg/kg). Interventional Management of Stroke III randomized AIS patients to r-tPA plus endovascular therapy versus standard r-tPA. Albumin in Acute Stroke Part 2 randomized patients to albumin±r-tPA versus saline±r-tPA. Our aim was to compare outcomes in CLEAR-ER combination arm patients to propensity score-matched r-tPA only subjects in Albumin in Acute Stroke Part 2 and Interventional Management of Stroke III. Methods—: The primary outcome was 90-day severity-adjusted modified Rankin score (mRS) dichotomization based on baseline National Institutes of Health Stroke Scale. Secondary outcomes were 90-day mRS dichotomization as excellent (mRS, 0–1); mRS dichotomization as favorable (mRS, 0–2); and nonparametric analysis of the ordinal mRS. Results—: Eighty-five combination arm CLEAR-ER subjects were matched with 169 Albumin in Acute Stroke Part 2 and Interventional Management of Stroke III trials' r-tPA only patients (controls). Median age in CLEAR-ER and control subjects was 68years; median National Institutes of Health Stroke Scale in the CLEAR-ER subjects was 11 and in control subjects 12. At 90 days, CLEAR-ER subjects had a nonsignificantly greater proportion of patients with favorable outcomes (45% versus 36%; unadjusted relative risks, 1.24; 95% confidence intervals, 0.91–1.69; P =0.18). Secondary outcomes were 52% versus 34% excellent outcomes (relative risks, 1.51; 95% confidence intervals, 1.13–2.02; P =0.007); 60% versus 53% favorable outcome (relative risks, 1.13; 95% confidence intervals, 0.90–1.41; P =0.31); and ordinal Cochran–Mantel–Haenszel P =0.10. Conclusion—: r-tPA plus eptifibatide showed a favorable direction of effect that was consistent across multiple approaches for AIS outcome evaluation. A phase III trial to establish the efficacy of r-tPA plus eptifibatide for improving AIS outcomes is warranted.